Study of the Acetylation Pattern of Chitosan by Pure Shift NMR - Lopez J.M. (2020)
Chitosan is a biodegradable, antibacterial, and nontoxic biopolymer used in a wide range of applications including biotechnology, pharmacy, and medicine. The physicochemical and biological properties of chitosan have been associated with parameters such as the degree of polymerization (DP) and the fraction of acetylation (FA). New methods are being developed to yield chitosans of specific acetylation patterns, and, recently, a correlation between biological activity and the distribution of the acetylated units (PA: pattern of acetylation) has been demonstrated. Although there are numerous well-established methods for the determination of DP and FA values, this is not the case for PA. The methods available are either not straightforward or not sensitive enough, limiting their use for routine analysis. In this study, we demonstrate that by applying HOmodecoupled Band-Selective (HOBS) decoupling NMR on signals assigned by multidimensional Pure Shift NMR methods, PA can be easily and accurately determined on various chitosan samples. This novel methodology - easily implemented for routine analysis - could become a standard for chitosan PA assessment. In addition, by applying Spectral Aliased Pure Shift HSQC, the analysis was enhanced with the determination of triads. Copyright © 2020 American Chemical Society.